МОНГОЛД ТОТАЛИТАР ДЭГЛЭМ ТОГТОХОД ИНСТИТУЦИЙН (ДҮРМИЙН) ГҮЙЦЭТГЭСЭН ҮҮРЭГ - Ч.Тамир, (Politology, 2023)
The purpose of this research paper is to define the role of institutions and rules in the two different models of totalitarian regimes. Main hypothesis role of institution in totalitarian regime had increased after Stalin’s death. The author used institutional approach to this historical study. This research can prove that Politburo changed one article of the Party rule. As a result of this change Politburo received power from Central Committee of Party illegally. Since that time this change had been kept until the socialist system collapsed in 1990. MPRP’s Politburo had taken all power without any control from Central Committee and Assembly of the Party after making this revision. Therefore, I would conclude that Mongolian totalitarian system had changed from classic totalitarianism to collective totalitarianism. This change occurred in 1954.